Using the linear damage summation hypothesis in the fatigue tests analysis of titanium alloy pieces - Gnatyuk Evgeniya (Institut za istrazivanja i projektovanja u privredi, 2021)
This paper presents the results of fatigue tests of titanium alloy, and also describes the use of the hypothesis of linear damage summation when processing the results of fatigue tests. Based on the experiments, the endurance limit of the titanium alloy was determined, which lies in the range from 460 to 480 MPa with the number of cycles from 105 to 108. The purpose of the experiment was to determine the endurance limit of high-strength material, as well as a mathematical measurement of the expected destruction. In this study, empirical methods were used such as indirect observation of the object under study, description, and measurement of technical influences exerted on it by an artificial means, as well as linear regression analysis to establish the relationship between stress and durability. As a result of the experiment, fatigue curves were obtained for various probabilities, which give grounds to conclude that the use of the linear damage summation hypothesis in processing the results of fatigue tests entails a satisfactory practical accuracy of the calculation of endurance limit. This experiment is aimed at improving metal production by studying the quality of titanium alloy test pieces and performing mathematical analysis of possible problems arising in the process of its operational testing.